Designing Reliability Model based on Client-Server Architectural Style for Component Based System - Sharma, Arpita (My University, 2011)
Software development has come a long way from traditional software development, which is characterized by the structured programming paradigm introduced in the late 60’s and early 70’s to contemporary development practices, which characterize a software application as interacting, independent components. Modeling and estimating software reliability during testing is useful in quantifying the quality of the software systems. However, such measurements applied late in the development process leave too little to be done to improve the quality of the software system in a cost-effective way. Reliability, an important attribute, is defined as the probability that the system performs its intended functionality under specified design limits. We argue that reliability models must be built to predict the system reliability at the initial phases of development process, and specifically when the implementation artifacts are unavailable. A number of architecture-based software reliability models have been proposed by researchers which are used for predicting reliability. One of the categories of reliability models is state based model for terminating applications which uses control flow graph to represent the architecture of the system. In this thesis we extend an analytical model for estimating architecture-based software reliability. We extend the model by adding the client server architectural style in it.
M.E. (Software Engineering)
Keywords: Reliability Model; Architectural style; Component based system